Releated Factors To The Social Interactions Of School-Age Children During The Covid 19 Pandemic - Ning Arti Wulandari; Erni Setiyorini; Khusnul Arifianti (STRADA : Jurnal Ilmiah Kesehatan, 2021)
Social distancing is recommended to prevent transmission Covid 19. Countries have made policies to dismiss schools to prevent transmission to children. The situation will have an impact on children's social interactions. This study is to identify the factors that influence social interaction in school age children during the Covid 19 pandemic. The design of this study uses correlation. This research was conducted in June 2020, with interviews via videocall to 73 respondents . The results showed that there was a relationship between children's social interactions with smartphone using intensitys (P value = 0,000) and parents' work (P value = 0.034), while the gender were unrelated. Data analysis uses multiple logistic regression. The covid 19 pandemic this has changed the pattern of communication into online, so that even though it is enacted psychically distancing pre-school age children can still do social interactions by using smart phones.